2016
DOI: 10.1002/2015jd024577
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol indirect effects from ground‐based retrievals over the rain shadow region in Indian subcontinent

Abstract: Aerosol‐induced changes in cloud microphysical and radiative properties have been studied for the first time using ground‐based and airborne observations over a semiarid rain shadow region. The study was conducted for nonprecipitating, ice‐free clouds during monsoon (July to September) and postmonsoon (October) months, when cloud condensation nuclei (CCN) concentrations over the region of interest increased monotonically and exhibited characteristics of continental origin. A multifilter rotating shadowband rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…Based on equation 1, values of the FIE at the SGP site in Figure 4 e phenomenon that increases in FIE as LWP increases at the SGP site is not consistent with that at the SACOL site. For current studies, the dependence of FIE on the LWP over California coast [64], the East China Sea [65], southeast Pacific [66], Nordic Countries [67], and Indian subcontinent [68] showed positive correlations, but it showed negative correlations at Pt. Reyes, California [69], and Azores [20].…”
Section: Aerosol Impact On Cloud Droplet Sizementioning
confidence: 67%
See 1 more Smart Citation
“…Based on equation 1, values of the FIE at the SGP site in Figure 4 e phenomenon that increases in FIE as LWP increases at the SGP site is not consistent with that at the SACOL site. For current studies, the dependence of FIE on the LWP over California coast [64], the East China Sea [65], southeast Pacific [66], Nordic Countries [67], and Indian subcontinent [68] showed positive correlations, but it showed negative correlations at Pt. Reyes, California [69], and Azores [20].…”
Section: Aerosol Impact On Cloud Droplet Sizementioning
confidence: 67%
“…For comparison purpose, all values are converted to the form (−z ln r e /z ln α) LWP , which is equivalent to ((1/3)(z ln N d /z ln α)) [72]. Different CCN proxies, such as aerosol number concentration, aerosol index, AOD, and aerosol scattering coefficient, would also bring discrepancy in FIE values, which were seldom considered in previous works [68,70,72]. In Figure 5, different CCN proxies are marked with different symbols.…”
Section: Aerosol Impact On Cloud Droplet Sizementioning
confidence: 99%
“…Under high-aerosol conditions, LWP changes little as LTS increases. A likely reason is inhibited cloud droplet sedimentation due to the reduced cloud droplet size, enhancing evaporation and entrainment at the cloud top and reducing LWP (Kaufman et al, 2005;Hill et al, 2009;Zhao and Garrett, 2015;Liu et al, 2016). There are similar variations in DER with increasing LTS under low-and high-aerosol conditions (bottom panels of Fig.…”
Section: Aerosol Effects On the Dependence Of Cloud Properties On Metmentioning
confidence: 73%
“…Over the Indian region, previous studies have compared MODIS-observed cloud microphysical properties between low-and high-aerosol loading to demonstrate the aerosol microphysical effect and its linkage to interannual variations in seasonal rainfall (Abish and Mohanakumar, 2011;Panicker et al, 2010;Ramachandran and Kedia, 2013). Aerosol impacts on cloud microphysics over central India based on ground-based measurements are also evident (Harikishan et al, 2016;Tripathi et al, 2007). Aircraft measurements during the CAIPEEX campaign over the ISMR have provided unprecedented evidence of the aerosol microphysical effect on cloud droplet distribution and warm rainfall suppression over the ISMR (Konwar et al, 2012;Pandithurai et al, 2012;Prabha et al, 2011).…”
Section: The Effect Of Underrepresentation Of the Wet-scavenging Effementioning
confidence: 97%